Feasibility study of green insulation materials including tall oil: Environmental, economical and thermal properties - Balo, Figen (Elsevier Science Sa, 2015)
In the present work, insulation materials are produced by using clay (C), fly ash (FA), rice husk ash (RHA) and epoxidized tall oil (ETC)). Density and thermal conductivity properties of these materials are analyzed. Environmental and economical analyses of sample with code T36 as insulation material are numerically investigated by using a computer program developed in LINGO. The optimum insulation thickness of this insulation material applied externally on wall for Elazig city of Turkey, energy saving over a lifetime of 10 years, payback periods, sensitivity analysis and emissions of CO2-SO2 versus insulation thickness are calculated for the four energy types. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Epoxidized tall oil; Rice husk ash; Insulation material; LINGO optimization programme; Optimum insulation thickness